ALDEAMENTO SÃO JERÔNIMO DA SERRA: UMA ESTRATÉGIA PARA A TRANSFORMAÇÃO DO ESPAÇO SOCIAL DO KAINGANG - Bernarski , Jóice (2017)
The societies, states, cultures and territories are transformed by the disputes established between different social regions that claim the monopoly of power by the space. The lands north of Paraná were the scene of disputes between the various indigenous social regions during the historical process. Resulting from these conflicts from the seventeenth century, these lands became territory of the Kaingang. In order to facilitate colonization, the empire built several villages in the 19th century, which were intended to bring the Indians together, civilize them to make them workers. These settlements contributed to consolidate the frontiers, as the Empire sought to build the nation based on civilization and progress. In this perspective, we will study the transformation of the social space of the Kaingang through the village of São Jerônimo da Serra, from 1859 to 1882, based on the documents selected from the Selective Catalog of Documents Concerning Indigenous Peoples in Paraná Provincial, available in the Public Archive of Paraná. These studies enabled us to show that even the indigenous peoples losing their territory resisted the process of colonization, in which they continued to be Kaingang. In this way, the village did not transform the cultural social space of the natives, who preserved their identity.